Multiplikasi Tunas dan Konservasi In Vitro Tanaman Belitung (Xanthosoma sagittifolium (L.) Schott) dengan Metode Pertumbuhan Minimal - Muhamad Sabda; Nurwita Dewi (Jurnal AgroBiogen, 2016)
In Vitro Shoot Multiplication and Conservation of Belitung (Xanthosoma sagittifolium (L.) Schott) using Minimal Growth Conservation Method. Muhammad Sabda and Nurwita Dewi. Belitung is one of potential food crops which has a lot of benefit. Belitung germplasm collection was conserved in the field which is vurnerable to biotic and abiotic stress.  The purpose of this research was to study the effect of  BAP on in-vitro shoot multiplication of belitung, and to study influences of osmoticum (mannitol) and retardan (paclobutrazol) to the growth of belitung culture. Experimental design used in this research was randomized completely design  with three  replications.  Shoot from sucker were used as explant. In study of shoot multiplication, the treatment medium was MS +  BAP (0, 1, 2, 3 mg/l). In study of conservation, the treatment medium was MS + 30 g/l sucrose, ½ MS + 30 g/l sucrose, MS + 15 g/l sucrose, MS + Mannitol (20,  40 and 60 g/l) and MS + Paclobutrazol (1, 2 and 3 mg/ l). The result showed that the addition of Benzyl Amino Purine (BAP) into MS medium increased number of shoot of belitung.  The best medium for micropropagation of belitung germplasm was MS + BAP 3 mg/l. The highest number of shoot (7.6 shoots) was produced by MS +  BAP 3 mg/l medium.  MS + mannitol (20 and 40 g/l) and MS + paclobutrazol (1, 2, and 3 mg/l) medium could reduce the  plant growth. MS + Paclobutrazol 2 mg/l was the best medium for belitung conservation. This media could reduce plant growth during eight months conservation period and prolong subculture interval.